Difference in white matter microstructure in differential diagnosis of normal pressure hydrocephalus and Alzheimer's disease - Hořínek, Daniel; Štěpán-Buksakowska, Irena; Szabó, Nikoletta; Erickson, Bradley J; Tóth, Eszter; Šulc, Vlastimil; Beneš, Vladimir; Vrána, Jiří; Hort, Jakub; Nimsky, Christopher; Mohapl, Milan; Roček, Miloslav; et al. (Clinical neurology and neurosurgery, 2016)
OBJECTIVES: Alzheimer's disease (AD) and normal pressure hydrocephalus (NPH) are both associated with cognitive decline and ventriculomegaly. While promising approach in differentiating between the two diseases, only a few diffusion tensor imaging (DTI) studies compared directly NPH and AD patients. The current study compares global whitematter (WM) alterations in AD and NPH addressing some of the methodological issues of previous studies. PATIENTS AND METHODS: Diffusion tensor images were obtained from 17 patients with NPH, 14 with AD, and 17 healthy controls. White matter integrity was quantified by fractional anisotropy (FA), mean (MD), axial (λ1) and radial diffusivity (RD). The diffusion parameters were compared between the groups in 'skeletonised' tracts representing the core of the fibre bundles. RESULTS: Reduced FA was found in NPH patients throughout the corpus callosum, particularly in the splenium, along with increased RD. On the other hand, FA, MD and RD were higher in NPH in the cortico-fugal fibres arising from the frontal and parietal cortex. While no FA changes were detected in AD patients compared to controls, widespread increased RD was observed. When comparing NPH and AD patients, higher FA, MD and RD was observed in the corona radiata in the periventricular fibres arising from the frontal and parietal cortex in NPH patients. The ventricular volumes were correlated with diffusivity parameters in the tracts next to the ventricles in AD and NPH patients. CONCLUSION: Our analysis identified a pattern of WM diffusion alterations that can differentiate NPH patients from controls and AD patients.
Keywords: White matter; Alzheimerova nemoc; senioři; TBSS; Aged; Male; lidé; lidé středního věku; Humans; Middle Aged; Diffusion Tensor Imaging; Normal pressure hydrocephalus; anizotropie; senioři nad 80 let; Aged, 80 and over; zobrazování difuzních tenzorů; mužské pohlaví; MRI; Alzheimer's disease; bílá hmota; Anisotropy; Hydrocephalus, Normal Pressure; White Matter; normotenzní hydrocefalus; ženské pohlaví; Alzheimer Disease; Female; DTI; diferenciální diagnóza; Diagnosis, Differential